Factors That Influence Eco-Friendly Product Purchasing Decisions: A Theoretical Approach - Ayuningtyas; Siti Nurjanah; Rd. Tuty Sariwulan; Suparno (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the factors that influence the purchase decision of environmentally friendly products through a comprehensive theoretical approach. Using the PRISMA 2020-based Systematic Literature Review (SLR) method, this study examines ten major relevant journals in the 2020–2024 period. The results show that individual factors such as environmental knowledge and awareness, as well as attitudes, play an important role in shaping purchase intentions and behaviors. On the other hand, social norms and green marketing also influence behavior through the mediation of environmental attitudes. Contextual factors such as the credibility of eco-labels and ease of access to products are moderators in the relationship between intentions and actual behaviors. This study concludes that the integration of individual, social, and contextual factors is essential to understand the complexity of eco-friendly product purchasing decisions. The implications of the research include strategic recommendations for companies and policymakers to encourage the adoption of sustainable consumption.